变频器装置以及依据漏电流值而选择性输出电流的方法 (2023)
本发明提供一种变频器装置包含一变频器模块、一输出滤波器、一旁通电路、一漏电流检测电路及一控制模块，变频器模块电性连结于一市电电源，输出滤波器电性连结于变频器模块与一负载，旁通电路与输出滤波器并联设置。在上述变频器装置的基础下，一种依据漏电流值而选择性输出电流的方法，主要是利用漏电流检测器检测输出滤波器与负载间的一漏电流值；然后利用控制模块比较漏电流值是否大于一漏电流限制值；最后，当漏电流值大于漏电流限制值时，控制模块发送一断路信号至导通开关，以驱使导通开关由预设的导通状态切换至断路状态。 The invention provides a frequency converter device which comprises a frequency converter module, an output filter, a bypass circuit, a leakage current detection circuit and a control module, wherein the frequency converter module is electrically connected to a mains supply, the output filter is electrically connected to the frequency converter module and a load, and the bypass circuit and the output filter are arranged in parallel. On the basis of the frequency converter device, a method for selectively outputting the current according to the leakage current value mainly comprises the following steps of: detecting the leakage current value between the output filter and the load by using the leakage current detector; comparing whether the leakage current value is gre